Analyse Des Determinants De Linefficacite Technique Des Exploitations Familiales Rizicole Dans La Région De lExtreme Nord-Cameroun (Global Journal of Human-Social Science, 2021)
This article looks at the origin of the productive technical inefficiency of Rice family farms in the Far North region of Cameroon, particularly the Maga production basin, which is one of the largest rice production basins in the country. This product is characterized by low domestic production, so the direct consequence is the import of rice to satisfy local demand; Finally, to evaluate the productive capacity of rice-farming family farms in this production basin, we determine the technical productive efficiency of these rice-farming family farms using CRS and VRS technology to determine the productive inefficiency index; finally, to explain these different indices we use a simple Tobit model. The model shows that certain parameters are at the origin of the technical productive inefficiency in the basin. Among these parameters the services provided by SEMRY is one of the most significant variables of the model.
Keywords: DEA; technical inefficiency; rice